The Emergence of Renminbi as an International Invoicing Currency and The Spillover - Yuan, Yuan (Journal of Applied Business and Economics, 2018)
China has aggressively promoted Renminbi(RMB), or Chinese Yuan, to be the next international currency since 2005. Has China's effort been paid off as RMB gradually emerged as an invoicing currency? What are the spillover effects of the RMB internationalization on the current vehicle currency country, US, and the rest of the world? It's hard to estimate the externality of RMB internationalization because of the endogeneity of the regime change. We adopt a dynamic trading post model developed by (Rey, 2001) and (Devereux & Shi, 2013), that exchange rates, prices, consumption, and trade flows are endogenously determined. Hence we can solve the endogeneity and estimate the quantity of externalities by simulating the international goods and foreign exchange market. We find positive(negative) externality on import and export prices when RMB becomes an invoicing(reserve) currency in international trades. The externality on the real side of the economy, such as, export, import and real exchange rate, is significant only if RMB rises as an international reserve currency. The spillover effect is also sensitive to the relative size of China, which means the timing of RMB internationalization matters.